2011
DOI: 10.1088/0953-8984/23/35/355401
|View full text |Cite
|
Sign up to set email alerts
|

Carbon release by selective alloying of transition metal carbides

Abstract: We have performed first principles density functional theory calculations on TiC alloyed on the Ti sublattice with 3d transition metals ranging from Sc to Zn. The theory is accompanied with experimental investigations, both as regards materials synthesis as well as characterization. Our results show that by dissolving a metal with a weak ability to form carbides, the stability of the alloy is lowered and a driving force for the release of carbon from the carbide is created. During thin film growth of a metal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
(94 reference statements)
2
20
0
Order By: Relevance
“…This effect has been experimentally demonstrated in Refs. 7 and 25 and theoretically in a paper by Råsander et al 26 In the present study the Ti 0.6 Fe 0.4 C 0.5 films have a very low carbon content close to the limits of the homogeneity range for the pure carbide. Thus, the carbon diffusion effect should be rather small.…”
Section: A Phase and Microstructure Characterizationsupporting
confidence: 79%
“…This effect has been experimentally demonstrated in Refs. 7 and 25 and theoretically in a paper by Råsander et al 26 In the present study the Ti 0.6 Fe 0.4 C 0.5 films have a very low carbon content close to the limits of the homogeneity range for the pure carbide. Thus, the carbon diffusion effect should be rather small.…”
Section: A Phase and Microstructure Characterizationsupporting
confidence: 79%
“…For electrical applications Ni is a proper choice of transition metal as it is not expected to cause problems with hard oxides or corrosion. It has been shown theoretically that Ni destabilise TiC in the same manner as Al [20]. Ni may also catalyse graphitization [21] which is favourable for both conduction in the a-C matrix and for low friction.…”
Section: Introductionmentioning
confidence: 99%
“…2 The alloying reduces the otherwise strong covalent metal-tocarbon bonds that are prevailing in TMC, and it is more favorable for C atoms to diffuse to the surface by the creation of C vacancies in the TMC. [3][4][5] In experiments on thin films of nanocrystalline (Ti,M)C, where the carbide phase is embedded in an amorphous C matrix, i.e. (nc-(Ti,M)C/a-C), it has been shown that the alloying with weak carbide forming metals, M, yields a larger amount of C matrix in relation to the carbide phase for systems with identical carbon-to-metal ratio during growth compared to systems that only contain Ti and C. [2][3][4][5][6][7][8] Furthermore, it has been shown that during heat treatment at elevated temperatures there is also an increase of the C matrix phase for the alloyed samples which is not present in the binary systems.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In experiments on thin films of nanocrystalline (Ti,M)C, where the carbide phase is embedded in an amorphous C matrix, i.e. (nc-(Ti,M)C/a-C), it has been shown that the alloying with weak carbide forming metals, M, yields a larger amount of C matrix in relation to the carbide phase for systems with identical carbon-to-metal ratio during growth compared to systems that only contain Ti and C. [2][3][4][5][6][7][8] Furthermore, it has been shown that during heat treatment at elevated temperatures there is also an increase of the C matrix phase for the alloyed samples which is not present in the binary systems. [3][4][5] When used as a surface coating material, the ternary solutions yield a lower friction coefficient than the binary samples while maintaining a relatively high degree of hardness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation